PEMANFAATAN PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 OLEH GURU PPKN KELAS XI IPA III DAN IV SMA NEGERI 1 SUNGAI RAYA KABUPATEN KUBU RAYA - Nurjanah Nurjanah; Syamsuri Syamsuri; Shilmy Purnama (Jurnal Muara Pendidikan, 2021)
This study aims to determine the process of using online learning during the COVID-19 pandemic by PPKn teachers in class XI IPA III and IV SMA Negeri 1 Sungai Raya, Kubu Raya Regency. The research method used is descriptive in the form of qualitative research. The data sources for this study were 2 PPKn teachers and 1 school principal. Data collection techniques used are direct communication techniques, observation techniques, and documentation techniques. While the data collection tools used are interview guides, and documentation tools. The results of the research on the use of online learning during the COVID-19 pandemic by PPKn teachers for class XI IPA III and IV SMA Negeri Satu Sugai Raya, Kubu Raya Regency, have been carried out well. This is evidenced by the role of PPKn teachers in class XI IPA III and IV in the process of implementing learning using google meet, classroom, and whatsapp group.